2006
DOI: 10.1038/nsmb1042
|View full text |Cite
|
Sign up to set email alerts
|

Transcription promotes contraction of CAG repeat tracts in human cells

Abstract: Induced transcription through CAG repeats in human cells increases repeat contraction approximately 15-fold in both confluent and proliferating cells. Repeats are stabilized against contraction by siRNA knockdown of MSH2, MSH3 or XPA, but not by knockdown of MSH6, XPC or FEN1. These results define a pathway for CAG.CTG repeat contraction that is initiated by transcription, depends on elements of mismatch and nucleotide-excision repair and does not require DNA replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
229
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(248 citation statements)
references
References 13 publications
19
229
0
Order By: Relevance
“…FLAH25 human cells that consists of a selection marker, the HPRT (hypoxanthine-guanine phosphoribosyl transferase) minigene, containing a (CAG) 95 repeat tract driven by an inducible promoter ( Fig. 1A) (28). Using this assay, we can detect large CAG contraction events that reduce the size of the repeat tract from 95 to 38 units or fewer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…FLAH25 human cells that consists of a selection marker, the HPRT (hypoxanthine-guanine phosphoribosyl transferase) minigene, containing a (CAG) 95 repeat tract driven by an inducible promoter ( Fig. 1A) (28). Using this assay, we can detect large CAG contraction events that reduce the size of the repeat tract from 95 to 38 units or fewer.…”
Section: Resultsmentioning
confidence: 99%
“…FLAH25 cells were derived from the human fibrosarcoma HT1080 cell line. Construction of this cell line was described previously (28). FLAH25 cells carry a spontaneous nonreverting deletion of the single endogenous HPRT gene; an integrated plasmid that constitutively expresses rtTA protein, which is the reverse tetracycline repressor protein fused to the HSV VP16 activation domain (17); and a single copy of the HPRT minigene with a CAG 95 tract embedded in its single intron.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our observations are in keeping with these results, which are suggestive of an early embryonic phenomenon. In addition, recently, Lin et al 43 demonstrated that induced transcription of CAG repeats increased large repeat CAG contractions by 15-fold with no evidence of expansions. These observations may therefore help explain why AR CAG repeat contractions are limited to the prostate as the prostate, almost uniquely expresses higher levels of AR, at an early stage of development.…”
Section: Discussionmentioning
confidence: 99%